2016
DOI: 10.4155/fsoa-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Metabolic Profiling for Painless Diagnosis of Human Diseases and Disorders

Abstract: Metabolic profiling provides a powerful diagnostic tool complementary to genomics and proteomics. The pain, discomfort and probable iatrogenic injury associated with invasive or minimally invasive diagnostic methods, render them unsuitable in terms of patient compliance and participation. Metabolic profiling of biomatrices like urine, breath, saliva, sweat and feces, which can be collected in a painless manner, could be used for noninvasive diagnosis. This review article covers the noninvasive metabolic profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 108 publications
0
18
0
Order By: Relevance
“…Metabolome analysis of blood and urine samples from CRC patients were performed, and several studies reported relevant biomarkers for CRC[ 166 - 168 ]. However, the transient localization of faeces in the colon and rectum makes it an ideal matrix for gaining information about the health and pathological state of the colon and rectum, and thus for colorectal cancer diagnosis[ 169 ]. Faecal samples consist of a diverse range of endogenous metabolites including tumour cell metabolites and gut microbiota metabolites[ 169 ].…”
Section: Microbial Signatures In Crcmentioning
confidence: 99%
“…Metabolome analysis of blood and urine samples from CRC patients were performed, and several studies reported relevant biomarkers for CRC[ 166 - 168 ]. However, the transient localization of faeces in the colon and rectum makes it an ideal matrix for gaining information about the health and pathological state of the colon and rectum, and thus for colorectal cancer diagnosis[ 169 ]. Faecal samples consist of a diverse range of endogenous metabolites including tumour cell metabolites and gut microbiota metabolites[ 169 ].…”
Section: Microbial Signatures In Crcmentioning
confidence: 99%
“…A cancer biomarker can be broadly defined as an objectively measurable parameter characterizing: (i) a malignant process or (ii) a pharmacological response to therapy. Biomarkers can exist in the form of DNA, RNA, or protein molecules [3], although emerging metabolic approaches are enabling candidate cancer biomarker discovery of various metabolites in both the preclinical [5,6] and clinical setting [7][8][9]. Historically, the first cancer biomarkers, tumor specific antigen carcinoembryonic antigen (CEA), and urinary Bence Jones protein were identified in colon carcinoma by the research group of Gold and Freedman [10,11].…”
Section: Cancer Biomarkersmentioning
confidence: 99%
“…The use of non-invasive or minimally invasive methods for diagnosing or predicting the onset of disease or inflammation in real-time or categorising metabolic state patient-side is revolutionising human medicine (Mal 2016). New rapid and precise technologies for genomic, transcriptomic and metabolomic testing are constantly being developed and improved on.…”
Section: Introductionmentioning
confidence: 99%